2019
DOI: 10.2196/11330
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Telemedicine in Remote Orthopedic Consultations: Randomized Controlled Trial

Abstract: Background Telemedicine consultations using real-time videoconferencing has the potential to improve access and quality of care, avoid patient travels, and reduce health care costs. Objective The aim of this study was to examine the cost-effectiveness of an orthopedic videoconferencing service between the University Hospital of North Norway and a regional medical center in a remote community located 148 km away. Methods An economic evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
242
1
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(270 citation statements)
references
References 36 publications
6
242
1
13
Order By: Relevance
“…Additional reports have shown cost savings about travel and societal expenses with the implementation of remote orthopaedic consultations. 17 , 18 A systematic review by Torre-Diaz et al looked at the cost utility and cost effectiveness of telemedicine across all fields and found that a relative scarcity of the literature is seen on this topic. Some cost effectiveness studies reported that telemedicine was able to reduce costs, but not all supported this notion.…”
Section: Discussionmentioning
confidence: 99%
“…Additional reports have shown cost savings about travel and societal expenses with the implementation of remote orthopaedic consultations. 17 , 18 A systematic review by Torre-Diaz et al looked at the cost utility and cost effectiveness of telemedicine across all fields and found that a relative scarcity of the literature is seen on this topic. Some cost effectiveness studies reported that telemedicine was able to reduce costs, but not all supported this notion.…”
Section: Discussionmentioning
confidence: 99%
“…Außerdem sind Sensoren bereits so kostengünstig erhältlich, dass ihre Anwendung in der Überwachung von Therapien und Rehabilitationen realistisch ist. Die Vernetzung mit webbasierten Anwendungen macht den 1,82, p = 0,0030); das Konfidenzintervall lag jedoch innerhalb der Nicht-Minderwertigkeitsspanne [7][8][9]. Auch bei weiteren sekundären Endpunkten gab es keine signifikanten Unterschiede.…”
Section: Sensorgestützte Diagnostik Und Rehabilitationunclassified
“…Die Dauer der Konsultation betrug 20,9 min in der Standardsprechstundengruppe und 20,5 mininderTelemedizingruppe [7][8][9]. Auch hinsichtlich der OP-Indikationen (17 % in der Standardgruppe und 11 % in der Telemedizingruppe) und Komplikationen (21 % in der Standardgruppe und 17 % in der Telemedizingruppe) bestanden keine signifikanten Unterschiede [7][8][9]. Es bestand kein Unterschied in den "patient reported outcome measures" (PROM).…”
Section: Sensorgestützte Diagnostik Und Rehabilitationunclassified
See 2 more Smart Citations